Bacterial Lysis via Photocatalysis ‐ A Critical Mechanistic Review. Issue 8 (21st February 2020) - Gupta, Rimzhim; Modak, Jayant
Abstract: This Review discusses one of the most important area of photocatalytic reactions. In current research scenario, photocatalysis is well utilized strategy for a wide variety of applications including organic/ inorganic decontamination, solar fuel generation, microbial disinfection etc. This Review touches upon the mechanistic aspect of microbial disinfection, the growth in the research, issues to be addressed in future to make it a sustainable technology for this application. This Review discusses the fundamental understanding of photocatalysis, important strategies to tune their optical properties to enhance the spectral range of absorption in visible and near infrared wavelength region. Various photocatalysis reports these days don't focus on the stability, reusability and recovery of the photocatalysts. However, these issues are very important to deal with for large scale viability of the process. Therefore, we have tried to address these issues along with the detailed experimental information and eliminate the misconceptions about bacterial disinfection. The details provided in this Review would help the researchers working in this area to a large extent and would open various questions for them to answer. Abstract : Disinfect all the things : This Review touches upon the mechanistic aspects of microbial disinfection, the growth in the research, issues to be addressed in future to make it a sustainable technology. Discussed are the fundamentals of photocatalysis and important strategies to tune optical properties suitable for microbial disinfection.